농업관련 지적재산의 보호와 개발 전략 - 성명환 (한국농촌경제연구원, 2008)
This study's objective is to review the institutional aspects of intellectual properties and genetic resources situation, to evaluate economic value for intellectual property rights in agricultural sector, and then to suggest the development strategies and protections of intellectual rights. The main intellectual property rights in agricultural sector include patent on plant, protection of new plant variety and geographical indications. The plant variety protection was established by the Seed Industry Law along with the 1991 UPOV Act. The purpose of the Law is to develop seed industry and to stability of agriculture, forestry, and fishery by enacting provisions on protection of the breeder's right, management of variety performance, seed production, certification, marketing and etc. The National Seed Management Office, as an implementing agency for the Plant Variety Protection has been reorganized in 1998. The economic values of patent on plant, geographical indications and trademarks for specific crops were evaluated by the econometric methods. For example, this study is to estimate consumer’s marginal willingness to pay for geographical indication of Seongju melon. The result indicates that the estimated marginal willingness to pay for geographical indication is very meaningful. Consumers are willing to purchase geographical indication products even if its price is higher than ordinary agricultural products. Therefore, it can be concluded that consumers have very high reliability towards geographically indicated products. The concerns to the intellectual property rights in the agricultural sector are increased. Therefore, it should need a policy of the intellectual property rights in agriculture for protecting their rights. This study suggested strategies for strengthening the protection of new plant variety, applying R&D results to agricultural production, and activating the geographical indication for regional economy.